Learn Python in 7 Days - Das Bhaskar N; Mohit (Packt Publishing, 2017)
Python is a great language to get started in the world of programming and application development. This book will help you to take your skills to the next level having a good knowledge of the fundamentals of Python. We begin with the absolute foundation, covering the basic syntax, type variables and operators. We'll then move on to concepts like statements, arrays, operators, string processing and I/O handling. You'll be able to learn how to operate tuples and understand the functions and methods of lists. We'll help you develop a deep understanding of list and tuples and learn python dictionary. As you progress through the book, you'll learn about function parameters and how to use control statements with the loop. You'll further learn how to create modules and packages, storing of data as well as handling errors. We later dive into advanced level concepts such as Python collections and how to use class, methods, objects in python.